The Effect of Erythritol Injection in Decreasing of Abortion Rate in Local Breed Ewes - Maher Saber Owain; Mustafa Salah Hasan; Ali Ghazi Atiyah (Veterinary Medicine International)
This study designed to evaluate the effect of Erythritol injection in decreasing of abortion rate in local breed ewes. Fifty pregnant ewes from local breed aged 2–4 years with a history of abortion except G1, were fed ad libitum hay and grains with water. The study was carried out in Salah Aldein province at special farm at a period of July–November 2022. These animals were tests for brucella by using rose Bengal and ELISA at zero day for confirmation; these animals were divided into 5 groups: G1 was brucella −ve and pregnant at 60 days, G2 was brucella +ve and pregnant at 60 days, G3 brucella+ve pregnant animals and treated by antibiotics gentamicin 10%, 3 ml/animal for 3 days, G4 brucella +ve and pregnant and giving erythritol, 10 ml S/C of 10% solution (solve in water and glycerol), and G5 was brucella +ve, and all pregnant and giving Erythritol+ gentamycin 10%, 3 ml/animal for 3 days. The experiment takes 12 weeks. Blood was withdrawn at different times of experiment (0, 2 weeks and end of experiment). The seroprevalence of brucellosis was shown that all animals at G4 and G5 where seropositive after 14 days of experiment, at end of pregnancy the seropositivity were highly significantly in G4 and G5 as compared with another groups. The current results showed that percentages of abortion were higher in G2, followed by G3, while it has been reduced significantly in G4 and G1. In conclusion, Erythritol alone can decrease the rate of abortion by making the bacteria extracellular far from placenta and evading of infection by immunity and/or gentamicin injection. Also, erythritol can be used as elicit diagnosis of brucellosis in latent infected animals.